A qualitative study of mental health explanatory models, and the perceived impact of life experiences on mental health, in HIV infected adolescents in rural and urban Uganda - Nalukenge, Winifred (Centre for Public Mental Health, 2018)
Background: Survival of children and adolescents with HIV/AIDS has greatly improved with antiretroviral treatment. These young people now live with a chronic, rather than a fatal disease, which has brought into focus issues of quality of life, including the emotional and behavioral wellbeing of those living with the disease. HIV infection is associated with poor mental health and a high prevalence of behavioral and emotional problems in affected adolescents. Despite this burden of emotional and behavioral problems, the majority of HIV care services in sub-Saharan Africa do not have mental health care services specifically targeting adolescents with HIV. In order to address mental health in this population, it is important to explore their explanatory models to understand aspects such as how they view their symptoms, and what treatment or support they prefer. At the present time, research is scarce regarding explanatory models of mental disorders in HIV-positive adolescents and no study has been conducted in Uganda. This study aimed to address this gap by exploring the explanatory models of mental disorders and perceived daily life challenges in HIV-infected adolescents who had been diagnosed with a common mental disorder. Methods: This qualitative study was nested in a longitudinal epidemiological study that investigated prevalence, incidence and risk factors for mental health problems in HIV-infected children and adolescents in rural and urban Uganda. In-depth interviews were conducted with adolescents aged 12 to 17 years who had been diagnosed with depression, anxiety or attention deficit hyperactivity disorder (ADHD). Case vignettes were used to enable adolescents to talk about their experiences and daily life challenges. Written consent and assent were sought from caregivers and adolescents respectively. Data were processed and analyzed thematically. NVivo-11 was used to manage data for analysis. Results: Twenty-one adolescents participated in the study. Most adolescents (9/21) in the study were living with their grandparents. Twelve were in primary school and 4 had dropped out. The main findings were: (i) the adolescents had not been informed about their mental disorder diagnoses and none viewed their symptoms as illness, (ii) they attributed their symptoms to daily life problems, such as poverty and interpersonal relationship problems, and did not mention biomedical or spiritual causes, (iii) they thought that their symptoms would improve with time, and financial and emotional support were also important. Conclusion: The findings of this study highlight the need for action at the mental health policy and practice levels. The main areas for such intervention include mental health literacy, screening and intervention in healthcare settings, and psychosocial interventions in community and school settings for affected adolescents and their caregivers.